2021
DOI: 10.3390/plants10050894
|View full text |Cite
|
Sign up to set email alerts
|

Foliar-Applied Potassium Silicate Coupled with Plant Growth-Promoting Rhizobacteria Improves Growth, Physiology, Nutrient Uptake and Productivity of Faba Bean (Vicia faba L.) Irrigated with Saline Water in Salt-Affected Soil

Abstract: The continuity of traditional planting systems in the last few decades has encountered its most significant challenge in the harsh changes in the global climate, leading to frustration in the plant growth and productivity, especially in the arid and semi-arid regions cultivated with moderate or sensitive crops to abiotic stresses. Faba bean, like most legume crops, is considered a moderately sensitive crop to saline soil and/or saline water. In this connection, a field experiment was conducted during the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 76 publications
3
25
0
Order By: Relevance
“…The combined soil and foliar application of PGPMs and Si-ZnNPs, respectively, boosted the performance of the soybean plant to its maximum capacity, which reduced the ESP in the soil to 32.5% lower than control, while nodule DW increased by 19.1%, root length by 28.6%, and leaves area plant −1 by 36.3% over control ( Figure 1 ). These positive findings are in agreement with our previous work on faba bean [ 25 ], where the dual application of PGPR and silica recorded heavier nodule dry weight and root length.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The combined soil and foliar application of PGPMs and Si-ZnNPs, respectively, boosted the performance of the soybean plant to its maximum capacity, which reduced the ESP in the soil to 32.5% lower than control, while nodule DW increased by 19.1%, root length by 28.6%, and leaves area plant −1 by 36.3% over control ( Figure 1 ). These positive findings are in agreement with our previous work on faba bean [ 25 ], where the dual application of PGPR and silica recorded heavier nodule dry weight and root length.…”
Section: Discussionsupporting
confidence: 93%
“…Remarkable studies have been conducted on the growth and productivity of crops grown under drought and salinity stress, and significant applications have been evaluated for their ability in improving the growth and development of field crops cultivated under drought and salinity stresses, which consider as an innovative approach for sustainable agriculture [ 21 , 22 , 23 , 24 , 25 ]. Beneficial microorganisms in the rhizosphere have positive effects on plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high efficiency of PGPR could be due to its ability to give high seedling vigor with a free radical defense system [ 55 ]. In this concern, soil applications are found to augment the growth and yield of higher plants, particularly under abiotic stress [ 56 , 57 ]. Soil microorganisms shape global element cycles in life and death.…”
Section: Discussionmentioning
confidence: 99%
“…Onion plants exposed to water stress under salt-affected soil reduce the plant growth and development by interrupting various physiological characteristics, such as total chlorophyll, carotenoids, stomatal conductance, and relative water content in addition to biochemical properties like total amino acids, proline content, and total soluble sugars [25]. In the current study, it was found that total chlorophylls, carotenoids, stomatal conductance, relative water content, and total soluble sugars were significantly increased and total amino acids and proline content decreased due to the important role of dual application of soil amendment with biochar and foliar spraying with potassium humate which had the potentiality to stimulate the meristematic activity which increases cell division and enlargement [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional contents of onion were enhanced in potassium humate applied as the presence of biochar could have resulted in improved phenolic compound synthesis [28] which has to been linked to a positive relation between bulb carbohydrate, bulb soluble sugars, bulb protein, bulb flavonoid contents and potassium humate applied on onion. Bulb carbohydrate, bulb soluble sugars, bulb protein, and bulb flavonoid contents rely upon transported ions and organic solutes that are converted into glucose inside onion [17,25] where biochar and potassium humate application enhances glucose biosynthesis, contributing to improved quality traits in onion plants.…”
Section: Discussionmentioning
confidence: 99%